Differences in host breed and diet influence colonization by Campylobacter jejuni and induction of local immune responses in chicken - Han, Zifeng; Willer, Thomas; Pielsticker, Colin; Gerzova, Lenka; Rychlik, Ivan; Rautenschlein, Silke (Gut pathogens, 2016)
BACKGROUND: Chickens are regarded as the main reservoir for human campylobacteriosis. Little is known about the interaction between Campylobacter jejuni (C. jejuni) and chickens. This interaction may be influenced by the stage of maturation of the immune system, developing gut microbiota composition and other factors including breed and diet. Our aim was to investigate the impact of breed, and diet on C. jejuni colonization and host immune responses in chickens. Birds were inoculated with 104 colony forming units (CFU) of C. jejuni or diluent at one (Exp. 1) or 22 (Exp. 2) days post hatch. We compared local immune cell subpopulations, cytokine expression levels, and gut microbiota composition between broiler-type (BT) and layer-type (LT) birds fed with either commercial broiler feed (bf) or layer feed (lf). RESULTS: Lower colonization rates were observed in the older age group independent of breed and diet. Independent of breed, birds fed with bf showed higher CFU of C. jejuni compared to lf-fed groups. Campylobacter jejuni-inoculation had a significant effect on lymphocyte numbers and cytokine expression levels in BT birds independent of feeding strategy (p < 0.05). These effects were not detected in LT birds, only LT birds fed with bf showed a significant increase in IL-8-expression at 7 days post C. jejuni inoculation compared to LT-control birds (p < 0.05). Diet influenced gut microbiota composition in a comparable manner between BT and LT birds, but changes in microbiota composition associated with C. jejuni inoculation varied between breeds. CONCLUSIONS: Diet and breed influenced C. jejuni colonization, immune responses and microbiota composition to a different extent comparing between LT and BT birds. The mechanisms behind these differences have to be elucidated further. Our results suggest that selection for more resistant breeds in combination with adapted feeding strategies may help to reduce Campylobacter colonization levels in commercial poultry in the future.
Keywords: Gut microbiota; Campylobacter jejuni; Diet; Immune response; Breed